2008
DOI: 10.3174/ajnr.a0796
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Serial Change in the Lumen and Outer Wall of Vertebrobasilar Aneurysms

Abstract: BACKGROUND AND PURPOSE:Estimation of the stability of fusiform aneurysms of the basilar artery requires precise monitoring of the luminal and outer wall volumes. In this report we describe the use of MR imaging and 3D postprocessing methods to study the evolution of those aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Thrombus deposition and aneurysm morphometry, however, are inherently 3D, and a comprehensive evaluation of aneurysm geometric properties and how they evolve with time requires more sophisticated analysis. 28 While this may not be possible at many centers, it is clearly important to include the thrombosed component in any measures that are made. This represents an additional advantage of steady-state techniques, which are fast and readily adapted to 3D volumetric coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombus deposition and aneurysm morphometry, however, are inherently 3D, and a comprehensive evaluation of aneurysm geometric properties and how they evolve with time requires more sophisticated analysis. 28 While this may not be possible at many centers, it is clearly important to include the thrombosed component in any measures that are made. This represents an additional advantage of steady-state techniques, which are fast and readily adapted to 3D volumetric coverage.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the aneurysm lumen pursued here was similar to that reported previously(9). In brief, CE-MRA images were directly imported into a commercially available 3D data processing software package RapidForm® (INUS Technology, Seoul, South Korea) which allows creation of isosurfaces directly from a DICOM data set after the user chooses an intensity threshold.…”
Section: Methodsmentioning
confidence: 58%
“…In all cases, it is also impossible to assure that three linear measurements accurately reflect the global changes in lumen shape and size that might have taken place over time. We have previously reported on a quantitative method for measuring morphology change by determining lumenal volume changes from co-registered 3D volume sets acquired at different time points (8, 9). That method obviates the need for specifying optimal view planes or for achieving equivalent view angles at different time points.…”
Section: Introductionmentioning
confidence: 99%
“…In previously published in vivo aneurysm wall imaging studies, depiction of microstructures within aneurysm walls was limited by spatial resolution, [13][14][15] because wall thicknesses ranged from 20 to 500 m. 16,17 To date, there is only 1 report on intracranial vessel wall microstructures delineated with 7T MR imaging using an ultra-high ex vivo 0.11 ϫ 0.11 mm 2 resolution. 18 The study showed excellent correlation with the histopathologic findings.…”
Section: Discussionmentioning
confidence: 99%